P11.21.B Distinct age-related molecular and clinical features inIDH-Wildtype Glioblastoma. (5th September 2022) - Richter, S; Stasik, S; Schackert, G; Thiede, C; Krex, D; Juratli, T A
Abstract: Background: The incidence of IDH-wildtype Glioblastomas (IDH-wt GBM) are highest amongst the elderly. However, IDH-wt GBM can occur in younger patients, subsequently associated with a relatively better prognosis. We aimed for comprehensive molecular characterization of IDH-wt GBM in a cohort with large range of Age at onset (AAO) to investigate age-related molecular patterns with potential impact on clinical tumor features and patients′ outcome. Material and Methods: We performed Whole Exome Sequencing (WES) on 55 patients with IDH-wt GBM. Sanger Sequencing was utilized for the TERT-promotor region as well as selected candidate genes to validate the results of the WES. Moreover, Progression-free- and Overall survival (PFS, OS) data, clinical- and tumor features were collected. Results: The patients' median AAO was 58 yrs. (range: 22.9-70.8 yrs.). We divided our study cohort into three subgroups based on AAO quartiles for further analysis: Group A: 22.9-40.4 yrs. (Q1), Group B: 44.5-71.0 yrs. (Q2-3) and Group C: 72.7-79.8 yrs. (Q4). The median OS for all patients was 15.9 months with a PFS of 9.5 months. The median tumor volume at initial presentation was 43.8 cm3 and correlated with AAO: 63.6 cm3 (Group A) vs. 41.2 cm3 (Group C).We identified a median of 32 mutations per tumor. Exome and Sanger sequencing detected frequent alterations on TERT -promoter (76.4%) and EGFR (90.9% gain, 50.1% amplification, 29.1% mutation). Chromosome 7 gain (92.7%) and Chromosome 10 deletion (85.5%) occurred significantly less in younger patients (Group A vs. Groups B/C; p=0.037, p=0.013). However, other individual alterations did not correlate with AAO. Via clustering of various alterations (e.g. TP53, PDGFRA, ATRX ), we found an association between a proneural GBM signature and younger AAO (p=0.036). AAO itself had an independent impact on OS: 21.5 Mo. (Group A) vs. 10.1 Mo. (Group C). Moreover, we described TET1 -deletions on Chr. 10 in 90.1% of cases, which was not previously described in IDH -wt GBM. Bi-allelic TET1 deletions (32.7%) with concurrent EGFR -amplification had a significant impact on patient's outcome (OS 12.2 Mo. vs. 17.6 Mo.; p=0.013). Conclusion: Although GBM signatures showed subtle association with AAO, our data provides no evidence for an age-specific molecular pattern. The vast amount of detected alterations regardless of AAO underlines the overall heterogeneity of IDH-wt GBM. The cause of better prognosis at younger age remains unclear on a molecular explanatory approach. Finally, a bi-allelic deletion of TET1 may represent a relevant alteration in IDH-wt GBM.